Program Temukan, Obati, Sayangi Balita Stunting (TOSS) - Puteri, Nadia Alifia; Ismanto, Slamet Usman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the effectiveness of the Find, Treat, Love Stunting Toddlers (TOSS) program in Kutanagara Village. The research method used is a qualitative research method with data collection techniques through interviews, observation and documentation. The technique for determining informants used was a purposive sampling technique with 9 informants. The results of the research show that the implementation of the TOSS program in Kutanagara Village is running effectively because it is in accordance with the previously determined program objectives, namely to reduce the stunting rate in Garut Regency so that it can reach 14% in 2024. In addition, the results released from the implementation of the TOSS program show positive output, where there was a reduction in the stunting rate in Kutanagara Village from 50 toddlers to 32 toddlers. However, improvements are still needed at the program socialization stage because the dissemination of information related to the program directly and indirectly is still limited and not updated. Thus, to increase the effectiveness of the TOSS program, it is recommended to carry out outreach activities related to the TOSS program more intensely and up to date. Keywords: Effectiveness, Find, Treat, Love Stunting Toddlers (TOSS) Program, Stunting